Zero coefficient‐aware fast butterfly‐based inverse discrete cosine transform algorithm. Issue 2 (1st February 2016) - Park, Sang‐hyo; Choi, Kiho; Jang, Euee S.
Abstract : The latest video coding standards, including Moving Picture Experts Group‐4 (MPEG‐4) advanced video coding (AVC)/H.264 and high‐efficiency video coding (HEVC), use a discrete cosine transform (DCT) process as the core for compression efficiency, sacrificing the computational complexity at decoder. There have been a number of attempts to reduce the complexity of inverse DCT (IDCT). Butterfly‐based factorisation remains the most commonly used method for such a reduction. In this study, the authors propose a zero (Z) coefficient‐aware fast butterfly‐based IDCT algorithm for video decoding. They focus on a reduction in the computational complexity of the butterfly‐based 8 × 8 IDCT by removing the unnecessary computations of one‐dimensional (1D) IDCT kernels, and adaptively applying IDCT kernels based on the number of non‐Z DCT coefficients to speed‐up 1D data. Their experimental results show that the average operation numbers using the proposed IDCT is approximately half that for the 8 × 8 IDCT implemented in the MPEG‐4 AVC/H.264 and HEVC reference software. The improved computational complexity of the proposed method is demonstrated by measuring the running time, which requires only one‐half of the IDCT time using the reference software.